2019
DOI: 10.1177/1463949119888494
|View full text |Cite
|
Sign up to set email alerts
|

Children’s literature in China: Revisiting ideologies of childhood and agency

Abstract: In this article we consider historical and contemporary ideologies of childhood in China and critically examine notions of ‘child’ and ‘childhood’ in Chinese children’s literature. We analyse the themes and knowledge that relate to relevant historical and contemporary political events and policies, and how these contribute to the production of childhoods. We focus on three images of childhoods in China: the Confucian child, the Modern child and the Maoist child. Each of the images reflects a way of seeing, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The discourse analysis of the Guideline and the interviews with Chinese teachers indicate that a Confucian discourse is drawn upon to prioritise order, responsibilities, and collectivism, and thus remains a subtle underpinning but pervasive discourse of children's citizenship in the Chinese context. The findings in this research, in line with previous studies(Tesar et al, 2019;Li & Chen, 2017), have shown a syncretism of Confucianism and socialism, which prioritises moral values and collectivism, and positions young children as socially responsible citizens for a harmonious society. Further, this research has found that Taoist discourse prioritises children's individuality and diversity.…”
supporting
confidence: 92%
“…The discourse analysis of the Guideline and the interviews with Chinese teachers indicate that a Confucian discourse is drawn upon to prioritise order, responsibilities, and collectivism, and thus remains a subtle underpinning but pervasive discourse of children's citizenship in the Chinese context. The findings in this research, in line with previous studies(Tesar et al, 2019;Li & Chen, 2017), have shown a syncretism of Confucianism and socialism, which prioritises moral values and collectivism, and positions young children as socially responsible citizens for a harmonious society. Further, this research has found that Taoist discourse prioritises children's individuality and diversity.…”
supporting
confidence: 92%
“…Studies (Dembo, 1981; Hwang, 2012; Hábl, 2017; Li, 1999; Liu, 1999; Papalia et al, 1999; Shih, 2016; Shih and Wu, 2007; Tesar et al, 2019) show that the teaching concepts for the moral education of young children are the following:…”
Section: Teaching Concepts For the Moral Education Of Young Childrenmentioning
confidence: 99%
“…A humane preschool teacher must use various methods to educate and guide young children during moral teaching while respecting their moral subjectivity and refraining from compelling them to comply. Moral education must avoid indoctrination (Hábl, 2017; Tesar et al, 2019). Hwang’s study noted that good interactions enhance the effectiveness of moral education (Hwang, 2012).…”
Section: Teaching Concepts For the Moral Education Of Young Childrenmentioning
confidence: 99%
“…
Children acquire and inherit cultural values and rules by interacting with the surroundings they live in (Fleer, 2017). The surroundings include both physical and psychological contexts, such as children's play and literature, which mirror the cultural image of childhood (Frønes, 2009;Tesar et al, 2019). It is also important to pay equal attention to both "education" and "care" in early childhood, something that traditionally varies across diverse curricula and cultures (Ailwood, 2022).
…”
mentioning
confidence: 99%